Analisis Penerapan Budgeting dalam Pengelolaan Keuangan Pribadi: Studi Kasus Pada Mahasiswa UIN Sunan Gunung Djati Bandung - Zenny Pebrianti; Amia Putri Rafiani; Melani Aprilia; Rahil Aditiya Saputra; Suhendi Suhendi (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2026)
This study examines the implementation of budgeting in personal financial management among students of UIN Sunan Gunung Djati Bandung. The main issue addressed is the inconsistency between students’ financial knowledge and their actual financial behavior, particularly in managing daily expenses. This research aims to analyze the extent to which students apply budgeting practices and to identify factors influencing their financial management behavior. A descriptive quantitative approach was employed using a questionnaire distributed via Google Forms to 32 students selected through purposive sampling. The data were analyzed using descriptive statistical techniques, focusing on percentages to illustrate patterns of financial behavior. The findings reveal that although most students demonstrate a good understanding of financial concepts, the practical application of budgeting remains low and inconsistent. A significant proportion of students do not regularly record income and expenses, set clear spending limits, or consistently save. External factors such as social environment, digital exposure, and promotional influences, along with internal factors like low self-control and unexpected expenses, significantly affect financial discipline. In conclusion, effective budgeting among students is not solely determined by financial literacy but also by behavioral consistency and environmental influences.